2022
DOI: 10.1093/mnras/stac3619
|View full text |Cite
|
Sign up to set email alerts
|

X-shooter survey of young intermediate-mass stars – I. Stellar characterization and disc evolution

Abstract: Intermediate mass stars (IMSs) represent the link between low-mass and high-mass stars and cover a key mass range for giant planet formation. In this paper, we present a spectroscopic survey of 241 young IMS candidates with IR-excess, the most complete unbiased sample to date within 300 pc. We combined VLT/X-Shooter spectra with BVR photometric observations and Gaia DR3 distances to estimate fundamental stellar parameters such as Teff, mass, radius, age, and luminosity. We further selected those stars within t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…Despite this bias, HD 9672 (49 Cet) in our sample is potentially at an intermediate stage, as it has been characterized in different works as a debris disk (Zuckerman & Song 2012), albeit one with a large CO gas content (e.g., Moór et al 2019;Higuchi et al 2020), and as a Herbig Ae system (Vioque et al 2018). Similarly, HD 141569 in our sample has been considered a "hybrid" disk in the transition phase between a protoplanetary disk and a debris disk (Augereau & Papaloizou 2004;Miley et al 2018;Di Folco et al 2020;Gravity Collaboration et al 2021;Iglesias et al 2023). These targets may represent the bridge between protoplanetary and debris disks.…”
Section: Making Sense Of the Outliersmentioning
confidence: 80%
See 1 more Smart Citation
“…Despite this bias, HD 9672 (49 Cet) in our sample is potentially at an intermediate stage, as it has been characterized in different works as a debris disk (Zuckerman & Song 2012), albeit one with a large CO gas content (e.g., Moór et al 2019;Higuchi et al 2020), and as a Herbig Ae system (Vioque et al 2018). Similarly, HD 141569 in our sample has been considered a "hybrid" disk in the transition phase between a protoplanetary disk and a debris disk (Augereau & Papaloizou 2004;Miley et al 2018;Di Folco et al 2020;Gravity Collaboration et al 2021;Iglesias et al 2023). These targets may represent the bridge between protoplanetary and debris disks.…”
Section: Making Sense Of the Outliersmentioning
confidence: 80%
“…Thus, half of the A and B stars in this star-forming region do not show obvious signatures of accretion. Iglesias et al (2023) used a volume-limited sample (out to 300 pc) and found that only six out of 134 targets in their sample of young, intermediate-mass stars (1.5 M e M * 3.5 M e ) show the accretion signatures needed to designate them as Herbig Ae/Be stars. These results suggest that there is a significant population of A and B stars in our volume (out to 450 pc) that are analogous to the weak-lined T Tauri stars.…”
Section: Making Sense Of the Outliersmentioning
confidence: 99%
“…Hence, no reliable sources can be included from Gaia DR3 Apsis' catalogs of young stars. There are a few other spectroscopically characterized intermediatemass YSOs in the literature, which we have not considered to keep the sample as homogenous as possible (this includes some or all of the sources from Nuñez et al 2021;Shridharan et al 2021;Valegård et al 2021;Zhang et al 2022;Iglesias et al 2023;Kuhn et al 2023). We estimate that, within the distance range considered in the analysis and discussion of this work (350-4000 pc; see Section 3.2 and Figure 2), our sample contains at least 85% of the known and spectroscopically characterized intermediate-and high-mass YSOs.…”
Section: Sample Completeness and Biasesmentioning
confidence: 99%
“…We refer the reader to the works of Hunt & Reffert (2023) 2023) sample with the one in this work because there are significant differences between them. Although both samples were selected by demanding a certain IR-excess level, our selection often resulted in the presence of emission lines (mostly tracing active accretion; e.g., Vioque et al 2022;Brittain et al 2023) whereas the Iglesias et al (2023) selection did not (only six of their 220 stars have detected emission lines). This indicates that the sample considered in this work, even though it is representative in mass distribution of the IMF (Section 2), might be a subsample of the total Galactic population of intermediate-and high-mass YSOs; i.e., the subsample of sources with larger accretion rates.…”
Section: Kerr Et Al (2023)mentioning
confidence: 99%
See 1 more Smart Citation